Active battery balancing system for electric vehicles based on cell charger - Amin, Amin; Budiman, Alexander Christantho; Kaleg, Sunarto; Sudirja, Sudirja; Hapid, Abdul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Cell imbalance can cause negative effects such as early stopping of the battery charging and discharging process which can reduce its capacity. In the previous active balancing research, the energy used for the balancing process was taken from the cell or battery pack, resulting in drop of electric vehicle driving range. In this paper, a cell charger based battery balancing system is proposed with a reduction in the number of switches. The use of a cell charger aims to increase the usable energy of the battery pack, since the energy used for the balancing process is taken directly from the grid. The use of fewer switches aims to reduce the cost and space used on the battery management system (BMS) hardware. The charger used for the balancing process has a maximum current of 3 A and a maximum voltage of 3.65 V while the number of switches used is n+5 for n batteries. A 15S1P 200 Ah LiFePO4 battery pack consists of 15 cells used for testing purpose. The test results show that the time needed to equalize the 15 cell battery voltage reaches 6 hours from the difference between the highest and lowest battery cell voltages of 145.1 mV to 15.1 mV.